Biomarcadores no fígado de girinos de rã-touro (Aquarana catesbeiana, Shaw, 1802): Efeitos da exposição ao microplástico de polietileno e nanopartículas de dióxido de titânio isolados e conjugados - Santos, Camila Sena dos (Universidade Federal de São Carlos, 2025)
Microplastics and titanium dioxide nanoparticles are emerging pollutants that have negatively impacted several species of living beings through their toxic effects on organs, development, and performance. One group of vertebrates that has received little attention on this issue is amphibians, which are characterized by excellent bioindicators. Therefore, the objective of this study was to evaluate glucose, triglyceride, and protein levels after chronic exposure to polyethylene microplastics and titanium dioxide nanoparticles in the livers of bullfrog tadpoles. The tadpoles were exposed for 21 days to polyethylene microplastics (PE MP group, 60 mg/L), titanium dioxide nanoparticles (TiO2 NP group, 10 µg/L), and the combination of both compounds (MP+NP group). The data obtained generally revealed no significant differences in the concentrations of the biochemical components analyzed, suggesting these animals' adaptability to the adverse conditions to which they were subjected. Studies like this can serve as a basis for understanding the toxic effects on these animals, such as biomonitoring, which highlights the relevance of such results not only for the group of organisms analyzed, amphibians, but also for studies on the impact of such contaminants on other groups of living beings.
Biomarkers in the liver of bullfrog tadpoles (Aquarana catesbeiana, Shaw, 1802): Effects of exposure to polyethylene microplastics and isolated and conjugated titanium dioxide nanoparticles
Keywords: Ecotoxicologia; Contaminantes Emergentes; Anfíbios; Ecotoxicology; Emerging Contaminants; Amphibians; CIENCIAS BIOLOGICAS::BIOQUIMICA